PERSPEKTIF ISLAM TENTANG KEKERASAN SUAMI TERHADAP ISTERI - Irda Misraini (Marwah: Jurnal Perempuan, Agama dan Jender, 2015)
Violence committed against the husband and wife both physically and psychologically is very difficult to disclose, because the data does not exist, and the problem is considered a private matter. But for example, in the case of nusyuz or wife against husband, there is a religious legitimacy (Alquran 4:34), for a husband to beat his wife on the grounds of disobedience wife. So widespread belief among Muslims arise, that the husband the right to beat his wife. When traced the context of the verse then beating is the last alternative for a husband whose wife nusyuz after mau'izah (give good advice and separate beds.) In fact, the concept of violence in the form of beatings should be avoided and not to be carried out because the Prophet Muhammad as a role model Muslims never do the beating of his wife.